2006
DOI: 10.1089/jmf.2006.9.378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Policosanol on Patients with Ischemic Stroke: A Pilot Open Study

Abstract: Stroke is a major health problem worldwide. Its pharmacological management includes thrombolytic therapy for the acute phase and antiplatelet drugs for stroke recovery and prevention. Statins can help in the acute phase and in preventing stroke in secondary prevention patients. Policosanol is a cholesterol-lowering drug with concomitant antiplatelet effects, with protective effects in stroke models. This observational study investigated the effects of policosanol (20 mg/day) administered during the acute phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…These results are consistent with previous data of the effects of policosanol in patients with ischemic stroke obtained in two open, uncontrolled, long-term studies, whose designs had limitations for strong conclusions [17,18]. Benefits of poli + AS treatment on platelet aggregation were also seen.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with previous data of the effects of policosanol in patients with ischemic stroke obtained in two open, uncontrolled, long-term studies, whose designs had limitations for strong conclusions [17,18]. Benefits of poli + AS treatment on platelet aggregation were also seen.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies in stroke patients [17,18], poli + AS treatment was safe and well tolerated. No patient discontinued the study due to AE, the frequency of AE was low, and all AE were mild.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, policosanol has shown protective effects in experimental brain ischemia models [20,21], and long-term administered prevented the progression of carotid-vertebral atherosclerosis in humans [22]. Two open and long-term clinical studies found that the addition of policosanol to aspirin (AS) therapy was associated to very good neurological recovery [23,24], and a further double-blind, placebo-controlled study demonstrated that policosanol + AS treatment improved the neurological recovery and decreased platelet aggregation in patients with recent ischemic stroke [25].In light of this background, this study investigated the effects of the therapy with policosanol 20 mg/day + AS 125 mg/day (poli + AS) on the neurological outcome and plasma oxidative variables in patients who had suffered a recent ischemic stroke as compared to placebo + AS 125 mg/day (pla + AS).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The growing interest in extracting and using these alcohols is motivated by their medical [2][3][4] and agricultural applications. [5] Policosanols have demonstrated to be effective in the treatment of various chronic diseases including diabetes and hypercholesterolemia, [6,7] in the prevention and the treatment of cardiovascular diseases [8] and in inflammatory diseases. [9] Policosanols have also been widely investigated in the agricultural field, in particular after the discovery of 1-triacontanol (C 30 OH) in the 70s [10] as a potent plant growth promoting substance of many agricultural and horticultural crops.…”
Section: Introductionmentioning
confidence: 99%